Ethnomatematics Study on Ikat Woven Fabric of The Kwatek Lamalera - Lyany Elisabeth Gunu; Julie Hongki (ITM Web of Conferences)
Ethnomathematics is a mathematical activity that grows and develops in a culture and customs in a particular region. The purpose of this research is to examine the deepest fundamental activities in the ikat woven fabric of the Kwatek Lamalera based on the fundamental activities proposed by Bishop, namely counting, locating, measuring, designing, playing, explaining. This research used a qualitative research method with an ethnographic approach and The data collection method used were observation and interviews with several weavers in Lamalera Village. The data of this research will be divided into four classes, namely: (1) history and development; (2) manufacturing process; (3) motif; and (4) philosophical meaning. The results showed that the activities of counting and explaining were found in all classes, while the activities of measuring and locating were found in the first, second, and fourth classes. In addition, playing activities were found in the second and fourth classes, and designing activities were found in the second classes.